Laparoscopic Surgery or Conservative Treatment for Appendiceal Abscess in Adults? A Randomized Controlled Trial. Issue 2 (August 2015) - Mentula, Panu; Sammalkorpi, Henna; Leppäniemi, Ari
<x xml:space="preserve">Abstract</x> Objective: We hypothesized that immediate laparoscopic surgery for appendiceal abscess would result in faster recovery than conservative treatment. Background: On the basis of the retrospective studies, conservative management of appendiceal abscess is recommended as a first line treatment, but some controversy exists. Methods: Sixty adult patients diagnosed with appendiceal abscess were randomly assigned to either laparoscopic surgery (n = 30) or conservative treatment (n = 30). Hospital stay, recurrences, additional interventions, and complications within 60 days from randomization were recorded. Results: There was no difference in hospital stay: 4 days (interquartile range: 3–5 days) in the laparoscopy group versus 5 days (3–8) in the conservative group, P = 0.105. Patients in the laparoscopy group had 10% risk for bowel resection and 13% risk for incomplete appendectomy. There were significantly fewer patients with unplanned readmissions in the laparoscopy group: 1 (3%) versus 8 (27%), P = 0.026. Additional interventions were required in 2 (7%) patients in the laparoscopy group (percutaneous drainage) and in 9 (30%) patients in the conservative group (surgery), P = 0.042. Recurrent abscesses and failure to respond to conservative treatment were the main reasons for additional interventions. Open surgery was required in 3 (10%) patients in the laparoscopy group and in 4 (13%) patients in the conservative group. Postoperative complications occurred in 3 patients in laparoscopic group versus 2 patients in the conservative group. The rate of uneventful recovery was 90% in the laparoscopy group versus 50% in the conservative group, P = 0.002. Conclusions: Laparoscopic surgery in experienced hands is safe and feasible first-line treatment for appendiceal abscess. It is associated with fewer readmissions and fewer additional interventions than conservative treatment with comparable hospital stay.